Comparative Transcriptomics Analysis and Functional Study Reveal Important Role of High-Temperature Stress Response Gene GmHSFA2 During Flower Bud Development of CMS-Based F1 in Soybean - Ding, Xianlong; Guo, Qingling; Li, Qiang; Gai, Junyi; Yang, Shouping (Frontiers in Plant Science, 2020)
High temperature (HT) is one of the most important environmental factors that negatively impacts some soybean cytoplasmic male sterility (CMS)-based hybrid (F1) combinations yield. The response of soybean to HT, especially at male organ development stage, is poorly understood. To investigate the molecular mechanisms of the response from soybean CMS-based F1 male organ to HT, a detailed transcriptome analysis was performed during flower bud development of soybean HT tolerant and HT sensitive CMS-based F1 combinations (NF1 and YF1) under normal temperature and HT conditions. Obvious HT damage was observed by treated with HT on YF1, such as indehiscent anthers and decreased pollen fertility, whereas the male fertility of NF1 was normally. In total, 8784 differentially expressed genes (DEGs) were response to HT stress, which were mainly associated with anther/pollen wall development, carbohydrate metabolism and sugar transport, and auxin signaling. The qRT-PCR analysis and substance content detection also revealed that HT caused male fertility defects in YF1 by altering pectin metabolism, auxin and sugar signaling pathways. Most importantly, sugar signaling-PIF-auxin signaling pathway may underlie the instability of male fertility in YF1 under HT. Furthermore, HT induced the expression of heat shock factor (HSF) and heat shock protein (HSP) gene families. Overexpression of GmHSFA2 in Arabidopsis can promote the expression of HT protective genes (such as HSP20) by binding to the HSE motifs in their promoters, so as to improve the HT tolerance during flowering. Our results indicated that GmHSFA2, acted as a positive regulator, conferring HT tolerance improvement in soybean CMS-based F1. GmHSFA2 may be directly involved in the activation of male fertility protection mechanism in the soybean CMS-based F1 under HT stress.